2002
DOI: 10.1889/1.1827857
|View full text |Cite
|
Sign up to set email alerts
|

Organic EL materials based on styryl and amine derivatives

Abstract: Abstract— Excellent organic electroluminescent materials are needed in order to obtain color EL devices with high performance. We have succeeded in realizing bright and efficient devices with long lifetime in various color regions, based on styryl and amine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Figure shows the evolution of lifetime compared at the same initial luminance of 1000 cd/m 2 . ,,,,,,,, In case of missing data of the initial luminance, we used the simple extrapolation of the available data with eq and n = 1, even though it can lead to an overestimation of the lifetime data. Because of the fact that this extrapolation is only necessary for data mainly collected in the last century, this overestimation may be a tribute to the pioneering work of our colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the evolution of lifetime compared at the same initial luminance of 1000 cd/m 2 . ,,,,,,,, In case of missing data of the initial luminance, we used the simple extrapolation of the available data with eq and n = 1, even though it can lead to an overestimation of the lifetime data. Because of the fact that this extrapolation is only necessary for data mainly collected in the last century, this overestimation may be a tribute to the pioneering work of our colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…For fabricating efficient blue OLED devices with good chromaticity, we need to conduct further studies. [11][12][13] Tang et al 14) of Kodak found that a doped emitter can greatly increase electroluminescence (EL) efficiency, shift colors, and endure the operational stability of organic EL devices. Usually a host was doped with one kind of dopant, for example, tris-(8-hydroxy-quinoline)aluminum (Alq 3 ) doped with a Coumarin545 (C545) emitter for green and 4-(dicyanomethylene)-2-methyl-6-(p-dimethylaminostyryl)-4H-pyran (DCM) for red.…”
Section: Introductionmentioning
confidence: 99%
“…For effective blue OLEDs, host materials such as distyrylarylene derivatives and styrylamine are commonly used. With suitable dopant materials, devices show high efficiency, brightness and good color saturation [3][4][5]. However, lifetime issue is still one of the major concerns in such a device [6][7][8].…”
Section: Introductionmentioning
confidence: 99%